2022
DOI: 10.1021/acs.oprd.2c00321
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of C-Terminus Cysteine Peptide Acids

Abstract: Cysteine (Cys) is a key amino acid in many therapeutic peptides. For research and industrial purposes, solid-phase peptide synthesis is the method of choice for the preparation of most peptides. The solid-phase synthesis of C-terminal Cys peptide acids is problematic because it is accompanied by a side reaction, namely, the abstraction of α-H from the Cys residue, which leads to the formation of three side products: the epimer and two N-piperidinyl-Ala epimer peptides. Here, we used a chlorotrityl chloride res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In our previous study, the synthesis of linear somatostatin using 30 min (10 + 20 min) treatments with 20% Morph-DMF for Fmoc removal yielded unsatisfactory results, with the prevalence of several deletion sequences throughout the synthesis. 22 This result indicated that the lower base strength of Morph impeded complete Fmoc removal during synthesis, even when it was used in large excess.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, the synthesis of linear somatostatin using 30 min (10 + 20 min) treatments with 20% Morph-DMF for Fmoc removal yielded unsatisfactory results, with the prevalence of several deletion sequences throughout the synthesis. 22 This result indicated that the lower base strength of Morph impeded complete Fmoc removal during synthesis, even when it was used in large excess.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] In this regard, we recently reported the use of 30% 4MP in 0.5 M OxymaPure-DMF for Fmoc removal. 22 In this context, other secondary amines, such as pyrrolidine and piperazine (PPZ), have also been exploited on several occasions. For example, the use of PPZ supplemented with DBU in N-methylpyrrolidone (NMP) has been described to enhance the suppression of DKP formation in some sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Despite S t Bu being removed employing such a method, the yield of the final cyclic peptide was not satisfactory. The use of S t Bu highlights several side reactions such as exacerbated racemization and dehydro-alanine formation during the synthesis of C-terminal Cys peptide acid . All of these shortcomings have presented major impediments to the wider application of S t Bu. , …”
Section: Mixed Disulfide-based/reducing Agent Labile Groupsmentioning
confidence: 99%
“…Due to this particular property, also specific side reactions may occur on N-terminal Cys, such as thiazine formation, [47] Cys epimerization, and the nucleophilic substitution of the thiol group during SPPS protocols. [48] Native chemical ligation (NCL) is a reaction that involves a thioester and an N-terminal Cys, resulting in the formation of a native amide bond with a Cys in the conjugation point. [49] This characteristic can also be exploited to design orthogonal synthesis routes, discriminating among the different types of Cys.…”
Section: Reactions Involving N-terminal Cysmentioning
confidence: 99%
“…In comparison to other Cys, the N‐terminal ones present a unique 1,2‐aminothiol group, making them more suitable for chemoselective reactions, which can be exploited when the peptide contains more than one Cys residue. Due to this particular property, also specific side reactions may occur on N‐terminal Cys, such as thiazine formation, [47] Cys epimerization, and the nucleophilic substitution of the thiol group during SPPS protocols [48] …”
Section: Conjugation Reactionsmentioning
confidence: 99%